Induction of apoptosis by pyrazolo[3, 4-d]pyridazine derivative in lung cancer cells via disruption of Bcl-2/Bax expression balance. Issue 3 (1st February 2018) - Mohamed, Mervat S.; Abdelhamid, Abdou O.; Almutairi, Fahad M.; Ali, Ayat G.; Bishr, Mai K.
Graphical abstract: Highlights: A pyrazolo[3, 4- d ]pyridazine derivative, PPD-1, was synthesized and characterized. PPD-1 showed remarkable cytotoxicity against lung carcinoma cell line with favorable therapeutic ratio. It is concluded that PPD-1 induces apoptosis in lung carcinoma cell line via disruption of bcl-2/bax expression balance. Abstract: In the rapidly expanding era of cancer target therapy, regulators of apoptosis are emerging as attractive therapeutic targets. X-linked inhibitor of apoptosis (XIAP) is of specific interest owing to its characteristic overexpression in a wide variety of neoplasms, with a resultant survival advantage for tumor cells and treatment resistance. In this study, we examined three pyrazolo [3, 4- d ] pyridazine derivatives (PPDs) through molecular modeling and studied their modes of interaction with XIAP-BIR3 domain. PPD-1, which possessed the highest binding affinity with XIAP, was tested on A549 (lung cancer cell line); HCT-116 (colorectal carcinoma cell line); HEPG2 (liver carcinoma cell line), HFB4 (normal human skin melanocyte cell line) and WI-38 (human embryonic lung fibroblasts). In comparison to cisplatin as a positive control, PPD-1 yielded remarkable cytotoxicity on all cancer cell lines, with the highest anti-tumor activity on A549 and a favorable therapeutic ratio. Flow cytometry studies concluded that PPD-1 treatment induces Sub G1 and G2/M cell cycle arrest and apoptosis. The percentage of apoptotic cells in PPD-1 treated A549 cells was considerably higher than that in untreated cells (10.06% vs 0.57%, respectively). To further investigate the mechanism of induction of apoptosis by PPD-1, Real time-PCR was used to quantify the expression levels of key apoptotic regulators. Significant overexpression of the effector capsase-3, pro-apoptotic bax and tumor suppressor gene p53 were noted as compared to untreated cells (7.19 folds, 7.28 folds, and 5.08 folds, respectively). Moreover, PPD-1 inhibited the expression of the anti-apoptotic bcl-2 gene to 0.22 folds. These findings demonstrate that PPD-1 treatment disrupts the Bcl-2/BAX balance in lung cancer cell lines, leading to apoptosis induction possibly through intrinsic mitochondria-dependent pathway. These novel insights elucidate the mechanism of PPD-1 cytotoxicity in lung cancer cell lines and offer a promising therapeutic approach that needs further study.